The endothelium and the pathogenesis of atherosclerosis - Channon, K (2006)
The endothelium lining the vascular wall is a critical mediator of normal vascular homeostasis, playing important roles in blood pressure regulation, blood flow, inflammation and haemostasis. Abnormalities of endothelial function are a characteristic feature of vascular disease states and precede the development of atherosclerotic plaques. Understanding the biology of the endothelium in health and disease provides insights into vascular disease initiation and progression. Similarly, advances in our understanding of the biology of the atherosclerotic plaque has clarified relationships between cellular and molecular events in the vessel wall and clinical events, and has paved the way for existing and novel treatments to reduce plaque progression and clinical risk. © 2006 Elsevier Ltd. All rights reserved.